Lexical – Semantic Grouping Of The Verbs Of English And Uzbek Languages (The Peerian Journal, 2025)
This article investigates the features of linguistic unites in the modern linguistics, their semantic field, thematic and lexical – semantic grouping which is discussed in the works of world scientists.